Implementación de un dispositivo electrónico "trado" que permita el aprendizaje de la lengua de signos en tiempo real con personas con discapacidad auditiva, por medio de comandos de voz - Arechúa Batalla, Silvia Daniela (2022)
This research project is based on providing an alternative for learning sign language in stu- dents with hearing disabilities through an electronic device that allows feedback with their tutor, in this way their evolutionary progress in academic performance is understood. The absence of tools for learning signed language in children with hearing loss is the main prob- lem that exists today when interacting with society, technology is a fundamental pillar for the creation of devices developed with solidarity purposes for these people. It consisted in the realization of a device made up of two main components: a microcomputer and touch screen, through the experimental design proposed in the methodology of this project, each of the phases belonging to the process that was carried out for the device was developed, Through the use of the Google Assistant, the translation of the voice commands into sign language was carried out. With the use of parameters in the configuration of the main com- ponents, the limitations for the use of the device were established. Optimum results of the “Trado” device were demonstrated through performance tests. Keywords: Signed language, inclusion, feedback, hearing problems, teaching.